2017
DOI: 10.1293/tox.2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic hemangiosarcoma of the liver in a young rat

Abstract: Spontaneous hemangiosarcoma is generally uncommon in rats. Furthermore, there are only a few case reports in young rats. This report describes a spontaneous hemangiosarcoma in a young 7-week-old rat. At necropsy, no remarkable changes were noted in any organs including the liver. Histopathologically, multifocal small tumors were located mainly in the perilobular region of the liver. The tumors comprised polygonal to short spindle-shaped cells that showed cellular atypia and local infiltration. In the foci, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In one report, splenic hemangiosarcoma was observed in a 9-week-old SD rat, comprising a dense sheet of pleomorphic cells frequently observed in undifferentiated tumors and intravascular metastasis to the liver 8 . In another report, similar histological features were observed in metastasized hepatic hemangiosarcoma of a 7-week-old SD rat 9 . The morphological features of these case reports, including this case, reflect the unique characteristics of hemangiosarcoma in young SD rats: extremely undifferentiated histological images without formation of clear vascular structures.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In one report, splenic hemangiosarcoma was observed in a 9-week-old SD rat, comprising a dense sheet of pleomorphic cells frequently observed in undifferentiated tumors and intravascular metastasis to the liver 8 . In another report, similar histological features were observed in metastasized hepatic hemangiosarcoma of a 7-week-old SD rat 9 . The morphological features of these case reports, including this case, reflect the unique characteristics of hemangiosarcoma in young SD rats: extremely undifferentiated histological images without formation of clear vascular structures.…”
supporting
confidence: 71%
“…In addition, it has been reported that spontaneous hemangiosarcoma is commonly found in rats aged 91 weeks or older 6 . Only a few cases have been reported in young rats [7][8][9] . In this report, we elucidate the occurrence of spontaneous hemangiosarcoma in the spleen and liver of young rats and describe the histological, immunohistological, and ultrastructural features of this tumor.…”
mentioning
confidence: 99%
“…Alprazolam and DZP are among the most abused psychotropic substances. When combined with alcohol, they can potentiate the depressant effect of the central nervous system and are thus used as facilitating drugs for sexual abuse crimes [4, 5]. In instances of suspected misuse or acute intoxication related to BZDs, the toxicological analysis involves a three‐step process: initial screening for substance class identification, utilizing spectroscopic and/or chromatographic techniques for specific substance identification, and subsequent quantification of the BZD molecules [6].…”
Section: Introductionmentioning
confidence: 99%